2017
DOI: 10.1158/0008-5472.can-16-1627
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide CRISPR Screen Identifies Genes Critical for Resistance to FLT3 Inhibitor AC220

Abstract: Acute myeloid leukemia (AML) is a malignant hematopoietic disease and the most common type of acute leukemia in adults. The mechanisms underlying drug resistance in AML are poorly understood. Activating mutations in FMS-like tyrosine kinase 3 (FLT3) are the most common molecular abnormality in AML. Quizartinib (AC220) is a potent and selective second-generation inhibitor of FLT3. It is in clinical trials for the treatment of relapsed or refractory FLT3-ITD-positive and -negative AML patients and as maintenance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 54 publications
0
52
0
Order By: Relevance
“…In a separate but similar finding, a genome-wide CRISPR screen identified that loss of SPRY3, an intracellular inhibitor of FGF signaling, and GSK3, a canonical Wnt signaling antagonist, can also induce quizartinib resistance. 63 Deletion of these genes in the FLT3-ITD AML cell line MV4-11, conferred quizartinib resistance as evidenced by increased cell viability and increased downstream MAPK and Wnt signaling. 63 These findings were further confirmed in quizartinib-resistant AML patient samples.…”
Section: Extrinsic Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate but similar finding, a genome-wide CRISPR screen identified that loss of SPRY3, an intracellular inhibitor of FGF signaling, and GSK3, a canonical Wnt signaling antagonist, can also induce quizartinib resistance. 63 Deletion of these genes in the FLT3-ITD AML cell line MV4-11, conferred quizartinib resistance as evidenced by increased cell viability and increased downstream MAPK and Wnt signaling. 63 These findings were further confirmed in quizartinib-resistant AML patient samples.…”
Section: Extrinsic Resistance Mechanismsmentioning
confidence: 99%
“…63 Deletion of these genes in the FLT3-ITD AML cell line MV4-11, conferred quizartinib resistance as evidenced by increased cell viability and increased downstream MAPK and Wnt signaling. 63 These findings were further confirmed in quizartinib-resistant AML patient samples.…”
Section: Extrinsic Resistance Mechanismsmentioning
confidence: 99%
“…Previously, studies using CRISPR-Cas9 libraries were published. Most of these studies used the same type of genome-wide library, GeCKO CRISPR Library version 1 or 2, comprising of >120,000 sgRNAs targeting nearly the entire genome (53)(54)(55)(56). For example, Sustic et al identified the endoplasmic reticulum to nucleus signaling 1 (ERN1)-JNK-JUN pathway as a potential target for improving the anti-cancer effects of MET inhibitors in KRAS-mutated colon cancer (56).…”
Section: Dropout Viability Screening Under Drug Treatmentmentioning
confidence: 99%
“…We next investigated whether CDK6 upregulation might be associated with clinical 291 resistance in some cases. To facilitate this, we generated a 10-gene CDK6 expression 292 "signature" (Table S6) Several genome-wide CRISPR pooled screens have uncovered mediators of drug 325 resistance [53,54]. In this study, we used CRISPR screens to systematically characterize 326 resistance to BRAF inhibitor PLX-4720 in melanoma.…”
Section: Cdk6 Expression Is Negatively Associated With Overall Survivmentioning
confidence: 99%